How does law and policy support providers of NHS healthcare in England to respond to harm experienced by patients during the course of their treatment and care: A scoping review - Naomi Assame; Susan Greenhalgh; John Tingle; Gillian Yeowell (PLoS ONE, 2026)
Introduction Many countries have implemented laws and policies to help healthcare providers address patient harm. However, there is limited research on their effectiveness, especially in the context of England#39;s National Health Service (NHS). This scoping review asks: How does law and policy support NHS healthcare providers in England respond to harm?. Methods and analysis A scoping review methodology was applied to map and summarise the literature to date. MEDLINE, CINAHL, and Westlaw were searched to identify potentially relevant literature that had been published between 2000 and 2025. Literature was included if it addressed care delivery in England#39;s NHS and healthcare providers’ responses to patient harm. Two reviewers independently screened the literature identified from the search against the eligibility criteria. A grey literature search of the citations within the included records was then conducted to identify relevant law and policy that supports providers of NHS healthcare in England to respond to patient harm. A total of 121 records were reviewed: 63 peer-reviewed and 58 pieces of grey literature. Data were charted using a standardised data extraction form. Themes were developed through a combination of thematic and content analysis, then presented as a narrative synthesis. Conclusion The first of its kind, this scoping review identified English laws and policies that support NHS healthcare providers in England to respond to patient harm. It revealed the incongruent yet interdependent relationship that exists between England’s legal systems, healthcare policies and the promoted NHS values. The scoping review highlighted how organisational culture can overshadow law and policy and be the defining factor in how providers of NHS healthcare in England respond to patient harm. The impact of law and policy in curating organisational culture and response to patient harm is an area requiring further research. Ethics Ethics approval was not required for this review.